Die Grenzen der Erziehung revisited (Verlag Barbara Budrich, 2024)
100 years after the publication of Bernfeld's critique of pedagogy, it still seems deeply entangled in the tension between what is normatively required and what is possible. The volume analyses current issues in school and non-school practice both empirically and theoretically. What are the limits of education? How does pedagogy deal with these limits? The contributions examine the actuality of Bernfeld's critique on the basis of empirical manifestations as well as preconditions, conditions and logics of the discrepancy between demand and reality of pedagogical practice.